Moral Rights of “Jargon” As Intellectual Property - Ni Putu Paramita Dewi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Legal protection of "Jargon" as something that can be protected is experiencing difficulties. Protection of “Jargon” as Intellectual Property is experiencing obstacles. Identifying the type of Intellectual Property is problematic because it does not have a tangible form, either Copyright or Industrial Property Rights. Therefore, it can be used by other parties even though "Jargon" is closely related to a person's characteristics and is created based on the results of someone's creative thinking. This often happens in the creative industry, which is supposed to apply creativity without injuring other people's creativity. This article analyzes and identifies "Jargon" according to Intellectual Property Law. It is supported by scientific articles related to the discussion to find efforts that can be considered in giving awards to the originators of "Jargon." Prior notification or inclusion of professional credit must be done before other parties use someone's "Jargon" as a grant of Moral Rights to the originator. Mainly if "Jargon" is used as a brand, company/agency, title of event to be broadcast, or other creative ideas.